Impact of software architecture on execution time: a power window TACLeBench case study. (2019) - Li, Haoxuan; Meulenaere, Paul De; Mercelis, Siegfried; Hellinckx, Peter
Timing analysis is used to extract the timing properties of a system. Various timing analysis techniques and tools have been developed over the past decades. However, changes in hardware platform and software architecture introduced new challenges in timing analysis techniques. In our research, we aim to develop a hybrid approach to provide safe and precise timing analysis results. In this approach, we will divide the original code into smaller code blocks, and then construct a timing model based on the information acquired by measuring the execution time of every individual block. This process can introduce changes in the software architecture. In this paper, we use a multi-component benchmark to investigate the impact of software architecture on the timing behaviour of a system.